Research on coordination mechanism for fresh agri-food supply chain with option contracts. Issue 5 (7th May 2019) - Zhou, Linan; Zhou, Gengui; Qi, Fangzhong; Li, Hangying
Abstract : Purpose: This paper aims to develop a coordination mechanism that can be applied to achieve the channel coordination and information sharing simultaneously in the fresh agri-food supply chain with uncertain demand. It seeks to elucidate how the producer can use an option contract to transfer the risk caused by uncertain demand, impel the retailer to share demand information and improve the performance of supply chain. Design/methodology/approach: An option contract model based on the basic model of fresh agri-food supply chain is introduced to compare the production, profit, risk and information sharing condition of the supply chain in different cases. In addition, a case study focusing on the sale of autumn peaches produced by a local producer is investigated, which provides evidence of the applicability of the authors' approach. Findings: The optimal option contract can help the supply chain achieve channel coordination and reach Pareto improvement. In the meantime, such a contract will encourage the retailer to share market demand information with producer spontaneously and help maintain the strategic cooperation between two parties. Research limitations/implications: This paper considers a single-producer, single-retailer system and both of them are risk neutral. Practical implications: Presented results can be used as suggestions for improving the contract design of fresh agri-food supply chain in China and can also provide references for other countries with similar experiences as China in fresh agri-food production. Originality/value: This research introduces the option contract into fresh agri-food supply chain and takes information sharing and the risk caused by uncertain demand into consideration.